Visitantes florais e eficiência de polinização em Jacquemontia bracteosa Meisn (Convolvulaceae) em uma área no Semiárido brasileiro - Santos, Silvia Karla Dias dos (2013)
Convolvulaceae flowers are characterized mainly by being beautiful and ephemeral, attracting many visitor flowers that belong to different taxonomic groups. They are often found in open environments acting as an important food resource to flower visitors especially bees. This work aimed to investigate the interactions between insects and flowers of Jacquemontia bracteosa Meisn visitors (Convolvulaceae) identifying the pollinator potentials in a semi-arid area in the Northeast. The study was carried out from November 2011 to October 2012, when the morphology and floral biology and reproductive biology of J. bracteosa and floral visitors. The J. bracteosa flowers opened early morning and lasted less than 12 hours, being considered ephemeral. These were self-compatible breeding system, with fruiting by selfing and outcrossing. The flowers were visited mainly by Apidae family bees (females and males of Ancyloscelis apiformis, Ceratina aff maculifrons and Trigona spinipes) and family Halictidae (Augochlora spp). Other visitors were collected from flowers with its frequency below 1%. Among the floral visitors A. apiformis was considered the most efficient pollinator for showing behavior, frequency, and constancy on the flowers. Furthermore, these bees arrived soon when the flowers began to open and presented 90% of efficiency in tests with three visited flowers of J. bracteosa. Other bees as T. spinipes, Ceratina aff maculifrons, Exomalopsis analis, Exomalopsis sp1, and Pseudaugochlora sp1 may be considered potential pollinators because they present behavior and morphology compatible with the flowers.